Antimicrobial Edible Films and Coatings based on N, O-Carboxymethyl Chitosan incorporated with Ferula Asafoetida (Hing) and Adhatoda Vasica (Adulsa) extract. Issue 3 (3rd July 2022) - Dixit, Anand; Sabnis, Anagha; Shetty, Aditya
ABSTRACT: In this investigation, the effect of incorporation of Ferula Asafoetida (Hing) and Adhatoda Vasica (Adulsa) extract on N, O-Carboxymethyl Chitosan (CMC) films at various concentrations was explored. Physicochemical properties like water absorption capacity, water vapour permeability (WVP), and water solubility; optical properties and antimicrobial properties against E. coli, S. aureus, B. Subtilis and C. albicans were studied. Results showed that increasing the concentration of Ferula Asafoetida (Hing) extract the ZOI (Zone of Inhibition) increased from 6 mm to 12 mm against S. aureus, 6 mm to 7.5 mm against B. Subtilis and in the case of Adhatoda Vasica (Adulsa) extract there was an increment of ZOI from 0 mm to 15 mm against C. albicans. In both extract cases, the transparency decreased as the concentration of extracts in the formulation increased. It was also observed that incorporation of both the extracts in the structure of the biopolymer increased WVP of CMC films. The percentage solubility of the film incorporated with Adhatoda Vasica (Adulsa) extract was higher than that with Ferula Asafoetida (Hing) extract. Water absorption shows a decreasing trend as the concentration of Hing extract increases in the formulation, whereas the water absorption capacity above 80% was observed in the case of Adulsa extract incorporated films.